2019
DOI: 10.1001/jama.2019.10575
|View full text |Cite
|
Sign up to set email alerts
|

Association of Midlife to Late-Life Blood Pressure Patterns With Incident Dementia

Abstract: IMPORTANCE The association between late-life blood pressure (BP) and cognition may depend on the presence and chronicity of past hypertension. Late-life declines in blood pressure following prolonged hypertension may be associated with poor cognitive outcomes. OBJECTIVE To examine the association of midlife to late-life BP patterns with subsequent dementia, mild cognitive impairment, and cognitive decline. DESIGN, SETTING, AND PARTICIPANTS The Atherosclerosis Risk in Communities prospective population-based co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
206
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(236 citation statements)
references
References 41 publications
14
206
2
3
Order By: Relevance
“…This is consistent with previous studies which reported that post-stroke dementia is more prevalent in men [50]. In large-scale populationbased cohort studies on the association of cardiovascular risk [51] and blood pressure pattern [52] with cognitive function, researchers have consistently reported that mid-life vascular disease has a more substantial effect on dementia onset. Our ndings highlight the importance of midlife as a critical period for later cognitive function.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies which reported that post-stroke dementia is more prevalent in men [50]. In large-scale populationbased cohort studies on the association of cardiovascular risk [51] and blood pressure pattern [52] with cognitive function, researchers have consistently reported that mid-life vascular disease has a more substantial effect on dementia onset. Our ndings highlight the importance of midlife as a critical period for later cognitive function.…”
Section: Discussionsupporting
confidence: 92%
“…It has been also found that in contrast to vascular dementia, where an increased level of Aβ peptide is observed, the dementia level of AD is linked with a low level of Aβ peptide [ 85 ]. This strong impact of midlife chronic hypertension on the increased risk for dementia in later life has been supported by a 24-year follow-up study carried out on 4751 individuals [ 86 ]. Surprisingly, a protective function of high blood pressure in the oldest-old has been found for individuals with hypertension developed in late life [ 87 ].…”
Section: Other Established (Non-)modifiable Risk Factors and Possimentioning
confidence: 93%
“…high total cholesterol (TC) and low high-density lipoproteins-cholesterol (HDL-C) are also independent risk factors of cardiovascular disease and cerebrovascular disease [5]. However, there has been no correlation analysis between change in blood pressure and HDL-C in general population.Hypertension in midlife is also a strong and independent risk factor of Alzheimer's disease and vascular dementia in late-life [6,7], because individuals who develop hypertension earlier in life are likely to be exposed to the deleterious neurological effects of hypertension for many decades. The higher midlife BP was associated with incidence of dementia in late-life [6].…”
mentioning
confidence: 99%
“…However, there has been no correlation analysis between change in blood pressure and HDL-C in general population.Hypertension in midlife is also a strong and independent risk factor of Alzheimer's disease and vascular dementia in late-life [6,7], because individuals who develop hypertension earlier in life are likely to be exposed to the deleterious neurological effects of hypertension for many decades. The higher midlife BP was associated with incidence of dementia in late-life [6]. Interestingly, subjects with midlife hypertension and late-life hypotension had a 4.26-fold higher risk of dementia.…”
mentioning
confidence: 99%